Parabolic almost contact structures - Baškienė, Angelė (Lietuvos matematikos rinkinys, 2001)
Parabolic analogues of almost contact structures are investigated. Parabolic (φ, ξ, θ, λ)- structure, parabolic metric (φ, ξ, θ, λ)-structure and its properties are defined.Existence of such a structures in hyperstufaces of almost dual spaces is proved; some examples of these structures are given.